BoPo on Instagram: An experimental investigation of the effects of viewing body positive content on young women’s mood and body image - Cohen, Rachel; Fardouly, Jasmine; Newton-John, Toby; Slater, Amy (New media & society, 2019)
Body-positive content on social media aims to challenge mainstream beauty ideals and encourage acceptance and appreciation of all body types. The present study aimed to investigate the effect of viewing body-positive Instagram posts on young women’s mood and body image. Participants were 195 young women (18–30 years old) who were randomly allocated to view either body-positive, thin-ideal, or appearance-neutral Instagram posts. Results showed that brief exposure to body positive posts was associated with improvements in young women’s positive mood, body satisfaction and body appreciation, relative to thin-ideal and appearance-neutral posts. In addition, both thin-ideal and body-positive posts were associated with increased self-objectification relative to appearance-neutral posts. Finally, participants showed favourable attitudes towards the body positive accounts with the majority being willing to follow them in the future. It was concluded that body-positive content may offer a fruitful avenue for improving young women’s body image, although further research is necessary to fully understand the effects on self-objectification.